2018
DOI: 10.5539/ies.v11n5p133
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Influencing Satisfaction of the University Students Who Work as Private Tutors

Abstract: Private Supplementary Tutoring (PST) have attracted enormous attention in recent days. Bangladesh experiences both forms of PST -formal and informal. There is a considerable amount of research based on the demand-side of PST. The tutors, who are the suppliers of PST in the market, are the center of attention in this paper. The forces that affect the satisfaction of a tutor from providing tuition have been investigated here through factor analysis and stepwise regression. Analyzing a set of tutors from Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Disadvantageous factors of tutoring such as loss of productive time, hindering academic results, and lack of recreation reduce the level of satisfaction. Tutors are thought to be self-focused as the outcome and improvement of the tutored are absent from the formulation of their satisfaction; therefore, closing a gap in the feeling of companionship between tutors and students will improve the quality of education [35]. In Table 2, it was found that, satisfaction with the university tutor is associated with the factors sex, age and college of origin, obtained a Chi-square x2 = 189.618a, 157.728a and 118.106a respectively, p < 0.05 and it is established that personal conditions are associated with satisfaction with the university tutor in engineering students.…”
Section: Research Articlementioning
confidence: 99%
“…Disadvantageous factors of tutoring such as loss of productive time, hindering academic results, and lack of recreation reduce the level of satisfaction. Tutors are thought to be self-focused as the outcome and improvement of the tutored are absent from the formulation of their satisfaction; therefore, closing a gap in the feeling of companionship between tutors and students will improve the quality of education [35]. In Table 2, it was found that, satisfaction with the university tutor is associated with the factors sex, age and college of origin, obtained a Chi-square x2 = 189.618a, 157.728a and 118.106a respectively, p < 0.05 and it is established that personal conditions are associated with satisfaction with the university tutor in engineering students.…”
Section: Research Articlementioning
confidence: 99%
“…In Sweden, most tutors are university students who are employed or volunteer a couple of hours each week for a shorter period, earning no or very little money from it. This makes Sweden stand out in comparison with many other countries, where students and teachers work as tutors for longer periods to make ends meet (e.g., Imtiaz, 2018; Popa & Acedo, 2006; Silova, 2010). An interview study with 27 university students working as tutors in for-profit and nonprofit settings in and around big city areas in Sweden paints a picture of the Swedish tutor as a female psychology student who spends 2–4 hr a week volunteering as a tutor for nonprofit organizations (see Appendix A for sample description).…”
Section: Tutor and Tutee Relationships And Social Identities In Diffe...mentioning
confidence: 99%
“…There is no doubt that tutors other than teachers also provide tutoring services in the above-mentioned countries. Nevertheless, research on ST shows that teachers figure more often as tutors in some countries with long histories of private ST. Students often figure as tutors in many parts of the world as well, for example, in Bangladesh (Imtiaz 2018) and the Czech Republic (Šťastný 2017). In an overview of for-profit ST in the European Union Bray (2011Bray ( , 2020 showed that private tutors in some Western European countries such as Belgium, Denmark, and Sweden (see Hallsén and Karlsson 2019 for more about tutors in Sweden) are often university students without any professional tutor or teacher training.…”
Section: Research On Private Tutorsmentioning
confidence: 99%